Speak Up Please! Teachers' Strategies in Teaching Speaking Skills at Vocational High School in Sidoarjo - Fatahillah, Muhammad Erwin; Agustina, Sheila (Jambura Journal of English Teaching and Literature, 2024)
Teaching speaking skills is an important part of foreign language learning. This study aims to find out the student difficulties that teachers find when teaching speaking and to find what strategies teachers use in teaching speaking at a vocational high school in Sidoarjo. This research uses a qualitative method with a case study approach. The subjects of this research were two English teachers at the vocational high school. Data were collected by conducting observations, interviews, and learning documentation during and after class. The results showed that teacher 1 found difficulties due to lack of motivation, lack of practice, lack of vocabulary, nervousness, low grammar mastery, and pronunciation challenges. To overcome these difficulties, teacher 1 used 9 strategies including role-playing, presentations, describing pictures, telling pictures, discussions, word walls, brainstorming, interviews, and storytelling. Similarly, teacher 2 found lack of motivation, lack of practice, lack of vocabulary, nervousness, low grammar mastery, and pronunciation difficulties to be the causes of difficulties. Teacher 2 also used 9 strategies, with some strategies different from teacher 1. They are role-playing, discussion, storytelling, interview, reporting, playing cards, describing pictures, telling pictures, and brainstorming. Thus, teachers can overcome students' difficulties in speaking by using the strategies used.